Pengaruh Job Stress Terhadap Psychological Well-Being Melalui Social Support Sebagai Variabel Intervening - Arin Winda Sari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Employees with excessive workloads can cause job stress, impacting their psychological well-being. Social support is needed to improve the quality of employees' psychological well-being. This study aimed to analyze the impact of job stress on psychological well-being through the social support of employees. This type of research is quantitative, where all employees are the sample. Data collection uses a questionnaire with 45 employees as a population, but the questionnaire returned as many as 40 responses. Data on this research were analyzed using Partial Least Square (PLS) with SmartPLS 3.7.7 software. The results showed that job stress negatively and significantly affects psychological well-being and social support. Social support has a positive and significant impact on psychological well-being. Social support mediates job stress on psychological well-being. This research implies that employees have moderate job stress levels but high psychological well-being mediated by social support. Hence, companies need to be mindful of the job stress employees experience to maintain their psychological well-being.